Strategic analysis of the brazilian Application Service Providers (ASP) market (Revista Brasileira de Contabilidade e Gestão, 2013)
The objective of the research was to study the Brazilian market for Application Service Providers (ASP) under the strategic analysis main theories. An ASP is a company that provides a service under contract to provide, host and manage applications for remote clients. This business model has been made possible by advances in information technology and communications, and is especially attractive for medium and small companies. Although fairly recent, from the late 1990s, in the second decade of this century the term has fallen into disuse and was replaced by Software as a Service (SaaS). The model still faces difficulties in its adoption in Brazil and the world, and this paper presents a case study which allowed a strategic analysis of the ASP industry. The research consisted of an extensive field research conducting interviews with executives from 26 companies within the Brazilian ASP value chain, seeking to identify the key issues that were involved in the dissemination of the model. For the analysis of the industry were used most widespread concepts of strategic analysis, especially Porter (1979 and 1985), with its model of competitive analysis - "Five Forces" - and "Generic Strategies”. However, the findings of the research showed that other concepts need to be taken into account to capture the strategic complexities of the sector, notably the notion of "complementors" and “ecosystems” and search for strategies other than simply compete to have the "best product".
Keywords: Application Service Provider; software as a service; strategic analysis